An Adaptive Parallel Arithmetic Optimization Algorithm for Robot Path Planning - Ruo-Bin Wang; Wei-Feng Wang; Lin Xu; Jeng-Shyang Pan; Shu-Chuan Chu (Journal of Advanced Transportation)
Path planning is one of the hotspots in the research of automotive engineering. Aiming at the issue of robot path planning with the goal of finding a collision-free optimal motion path in an environment with barriers, this study proposes an adaptive parallel arithmetic optimization algorithm (APAOA) with a novel parallel communication strategy. Comparisons with other popular algorithms on 18 benchmark functions are committed. Experimental results show that the proposed algorithm performs better in terms of solution accuracy and convergence speed, and the proposed strategy can prevent the algorithm from falling into a local optimal solution. Finally, we apply APAOA to solve the problem of robot path planning.